Optimal exercise dose and type for improving sleep quality: a systematic review and network meta-analysis of RCTs - Li, Li; Wang, Chunxiao; Wang, Dandan; Li, Hua; Zhang, Shuai; He, Yuanchun; Wang, Ping (Frontiers in Psychology, 2024)
Background:The present study systematically evaluated the differential effects of various types of exercise,as well as exercise dosages (including duration,intervention period,frequency,and intensity), on sleep outcomes using a network meta-analysis approach. Methods:We rigorously selected the literature according to the PICOS principle, and two independent researchers extracted the data. We employed Revman 5.4 software for bias risk assessment and traditional meta-analysis, while Stata 17.0 software was utilized for network meta-analysis to generate network evidence plots and funnel plots. Furthermore, we adopted the surface under the cumulative ranking curve (SUCRA) to evaluate and rank the intervention effects of different exercise types and dosages on sleep quality. To verify the robustness of our study results, we performed a sensitivity analysis using the leave-one-out method. Results:The study strictly adhered to the PRISMA guidelines and included 58 RCT papers with a total of 5008 participants. The network meta-analysis revealed significant variations in the impact of exercise frequency on sleep outcomes when compared to the control group. Interventions of 1-2 times per week [SMD=-0.85,95% CI (-1.43,-0.26)], 3 times per week [SMD=-0.45,95%CI (-0.80,-0.11)], and 4 times per week [SMD=-1.09,95%CI (-1.92,-0.26)] demonstrated the most notable effects. Interventions lasting ≤30 minutes and 60-65 minutes were significantly more effective than the control group, with ≤30 minutes proving significantly more effective than 40-55 minutes [SMD=0.75, 95%CI (0.01,1.49)].Interventions lasting 9-10 weeks[SMD=-1.40,95%CI (-2.37,-0.44)],12-16 weeks [SMD=-0.55,95% CI (-0.90,-0.20)],and ≥24 weeks [SMD=-0.71,95%CI (-1.31,-0.10)] were all significantly more effective than the control group. Furthermore, interventions of moderate intensity [SMD=-1.06,95%CI (-1.52,-0.61)] and high intensity [SMD=-1.48,95%CI (-2.55,-0.40)] exercise interventions yielded significantly greater benefits compared to the control group. Specifically, high intensity interventions [SMD=-1.97,95%CI (-3.37,-0.56)] and moderate intensity [SMD=-1.55,95%CI (-2.57, -0.54)] exercise interventions were found to be significantly more effective than moderate-high intensity interventions. In terms of exercise types, aerobic exercise [SMD=-0.56,95%CI (-0.86,-0.27)], traditional Chinese exercises [SMD=-0.57,95%CI (-0.97,-0.18)], and combined exercise [SMD=-0.99,95%CI (-1.66, -0.32)] interventions all all produced significant improvements compared to the control group. Conclusion: The current evidence indicates that combined exercise with a frequency of 4 times per week, a duration of ≤30 minutes, a period of 9-10 weeks,and high intensity is most effective for improving sleep quality.